Malignant lung carcinoid tumour with liver and bone metastasis: a case report - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; Hassan, Nurhidayah; Harun, Norra; Abdul Ghani, Fatimatulzahra (2021)
Atypical lung carcinoid tumour, which is highly malignant has not been described widely in the literature. We report a middle-age woman who initially referred for possible lung malignancy. She presented with chronic diarrhoea to surgical team initially, who incidentally found to have a minimally enhancing irregular hypodense lesion at medial segment right lower lobe based on CT thorax finding. This patient later was diagnosed to have malignant lung carcinoid tumour based on histopathological examination with liver and bone metastasis. This case highlights the rare presentation of carcinoid tumour. A thorough history, supplemented by imaging and bronchoscopic examinations may lead to the diagnosis.